Diagnostic accuracy of computed tomography colonography in patients at high risk for colorectal cancer: a meta‐analysis. (27th April 2020) - Bai, W.; Yu, D.; Zhu, B.; Yu, X.; Duan, R.; Li, Y.; Yu, W.; Hua, W.; Kou, C.
Abstract: Aim: The aim was to explore the diagnostic value of computed tomographic colonography (CTC) compared with conventional colonoscopy in individuals at high risk for colorectal cancer. Method: PubMed, Embase, the Cochrane Library and the Web of Science were searched by two independent reviewers for potentially eligible studies published up to 31 October 2018 that were based on a per‐patient analysis. stata, meta‐disc and revman were used to perform this meta‐analysis. A random‐effect model was used, and a subgroup analysis was conducted to explore the sources of heterogeneity. Results: A total of 14 full‐text articles, involving 3578 patients, were included in this meta‐analysis. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio and the area under the summary receiver operating characteristic curve of CTC for detecting polyps ≥ 6 mm were 0.87 (95% CI 0.83–0.90), 0.90 (95% CI 0.86–0.93), 9.08 (95% CI 6.28–13.13), 0.14 (95% CI 0.11–0.18) and 0.94 (95% CI 0.92–0.96), respectively. For polyps ≥ 10 mm, the pooled sensitivity, specificity, positive likelihood ratio and negative likelihood ratio of CTC were 0.91 (95% CI 0.86–0.94), 0.98 (95% CI 0.95–0.99), 40.36 (95% CI 19.16–85.03), 0.90 (95% CI 0.06–0.14) and 0.98 (95% CI 0.96–0.99), respectively. Conclusion: In this meta‐analysis, CTC had high diagnostic accuracy for detecting polyps ≥ 6 mm and ≥ 10 mm in patients at high risk of developing colorectal cancer and it had a higher sensitivity and specificity for detecting polyps ≥ 10 mm than polyps ≥ 6 mm. However, the results should be used cautiously due to the significant heterogeneity.